Raspberries and gooseberries in south Patagonia: Production, fruit quality, morphology and phenology in two environmental conditions - Birgi, Jorge Alberto (2019)
Fine fruits as raspberry and gooseberries represent the second production with the largest area cultivated in Santa Cruz province (Argentina), and this activity is usually carried out by family farmers in outdoor conditions. The availability of information about productive, morphologic, phenological and quality aspects of these crops in south Patagonia is very scarce. The aim of this work was to evaluate performance of Rubus idaeus cv. Autumn Bliss (RIA), R. idaeus cv. Glean ample (RIG), Ribes rubrum (RR), Ribes nigrum (RN) and Ribes uva crispa (RU) under two environments: outdoors and in greenhouse. An essay with a split plot design, with environment as the main plot and the species as a subplot, with three replicates, was established. Variables related to morphology, phenology, fruit production and fruit quality were measured. Significant differences were found in fruit production according to environment. At the third year, fruit production in greenhouse was 19.6, 130.7, 626.2, 693.1 and 1308.7 g plant−1 for RIG, RR, RN, RIA and RU, respectively. In the same year, production outdoors was 14.3, 80.5, 84.6, 90.7, 343.1 RIG, RN, RR, RIA and RU, respectively. Environment also affected individual fruit weight, being 1.79 g the mean fruit weight in greenhouse and 0.98 outdoors. Morphologic variables had a strong influence on fruit production, mainly on node number and foliar area. Results showed a 65% higher mean production efficiency of plants (gr fruits/m2 foliar area) in greenhouse compared with outdoor plants. In general, raspberries in outdoor condition decreased 90% in production efficiency, whereas gooseberries decreased 40%. In average, RIA were the most efficient plants throughout all the study period and RU had the highest efficiency during the last year of production. In conclusion, outdoor production of these species in South Patagonia is not recommended, because temperature and wind intensity severely affected plant performance. However, if outdoor condition is the only option, cultivate RU is the best option.